"Urfolk" og "mangfold" i skolens læreplaner - Olsen, Torjer Andreas; Andreassen, Bengt-Ove (FLEKS - Scandinavian Journal of Intercultural Theory and Practice, 2018)
Source at https://doi.org/10.7577/fleks.2248 . Since 1974, the curriculum for the Norwegian school has had a overarching part that puts the school and its content into a bigger social and political context. As such, this part of the curriculum is a highly political and ideological text that expresses the state's purpose and interest related to the school. This article looks into how indigenous people, minorities and diversity is represented in the general part of the curriculum from 1974 to 2017. The changing curricula show changes in the official politics and views on diversity. Through an analysis of the curricula we explore which terms and concepts that are used in the description of people and groups in Norwegian society. We focus primarily on the representation of the Sami, who move from being people in "mixed language districts" with limited rights, via being an "ethnic minority", to being an indigenous people with a set of rights. Further, we look into how the diverse society is represented, from the use of "alien workers", via "immigrants", to just "diversity". We argue that the concepts or strategies of politics of recognition and politics of integration respectively can be used to describe the curricula. Norway's educational policy towards minorities and indigenous people seems to exist between these two. In the end, this leave diversity competence as an important concept in the future Norwegian school.